Statistical analysis of development geopolymer concrete with glass bubble toward thermal insulation performance - Shahedan, Noor Fifinatasha; Abdullah, Mohd Mustafa Al Bakri; Kusbiantoro, Andri; Tanyildizi, Harun; Hadibarata, Tony; Jusoh, Muhammad Noor Hazwan (Elsevier, 2024)
Optimal usage of glass bubbles as thermal insulation materials has developed geopolymer concrete and achieved good thermal properties that are different from traditional designs, thus improving the quality of precast construction in Malaysia. However, the present study of concrete is more focused on the physical and mechanical properties of the materials rather than statistical analysis. Measured results of t-test, Pearson correlation, and regression equation obtained from this study will envelop the relationship among the parameters; correlation contributes to the insulation performance and equation to be used as a guideline for producing any required performance. Based on the summary values of t-test, it can be concluded that at 95% confident level, there was significant difference with replacement volume fraction glass bubble toward thermal conductivity, thermal diffusivity, and also specific heat. A good correlation was found between glass bubble content and all the properties of the geopolymer concrete, which shows the potentially important value from 1.000 to 0.933 where, toward thermal conductivity (?0.575) and thermal diffusivity (?0.686), show possibly important. The regression equations display an equation for each combination of properties toward the volume fraction of glass bubble (compressive strength, 28 days=68.59-0.4148glass bubble; thermal conductivity=2.026-0.00839glass bubble; thermal diffusivity=1.535-0.00518glass bubble; and specific heat=1.2424+0.00867glass bubble). The statistical analysis helps this research to have better understanding of the data obtained and to produce better result and design at the same time helps to predict properties that want to be achieve in the future. © 2025 Elsevier Ltd. All rights reserved.
Keywords: geopolymer concrete; glass bubble; Pearson correlation; regression equation; Statistical analysis; t-test